A new Neotropical genus of the family Cunaxidae (Acari: Prostigmata: Bdelloidea) - Heyer, Jacob Den; de Castro, Tatiane Marie Martins Gomes (Zootaxa, 2008)
A new Neotropical genus and its species, Allocunaxa heveae gen. et sp. nov., is described and figured. The generic features are provided. The subfamily Cunaxinae is discussed and a key to it is provided.